Przyroda na usługach świętych na przykładzie św. Feliksa z Noli w "Natalicia" Paulina z Noli - Wysocki, Marcin (Vox Patrum, 2024)
After his conversion, every year on the feast of St Felix, which is celebrated on January 14, Paulinus of Nola wrote a work of praise in honour of his patron – the Natalicium. In the extant Natalicia (14 or 15), the miracles performed by Felix assume a significant position. Many of them are related to nature. The aim of this article is to show, through an analysis of the Natalicia, how nature is subjected to the miraculous actions of the saints, using St Felix as an example. From the presentation in this article of the miracles and extraordinary events that took place during the life of St Felix or after his death at his tomb, it is evident that Paulinus held the figure of St Felix in particularly high regard, referring to him as his father, protector and patron. Paulinus sets out to demonstrate the greatness of St Felix and his special place in the pantheon of saints by describing the miracles. Nevertheless, Paulinus consistently emphasises that the saint is merely an intermediary, and that the capacity to perform miracles ultimately resides with God, who is the Lord and Creator of all creation. Therefore, if Felix is depicted as governing over nature, which he does in a manner contrary to natural order, this is a consequence of Felix’s proximity to God. It is notable that Paulinus introduces a unique perspective in this regard, as there existed a precedent in pagan poetry for portraying miracles associated with animals. Nevertheless, Paulinus, while adhering to the literary tradition and language of Virgil, establishes a distinct tone and character. Natalicia exemplify Paulinus’ profound convictions, unwavering faith, and profound devotion to Felix.